The effect of air puff stress on c‐Fos expression in rat hypothalamus and brainstem: central circuitry mediating sympathoexcitation and baroreflex resetting. (12th March 2014) - Furlong, Teri M.; McDowall, Lachlan M.; Horiuchi, Jouji; Polson, Jaimie W.; Dampney, Roger A. L.
Abstract Psychological stress evokes increases in sympathetic activity and blood pressure, which are due at least in part to an upward resetting of the baroreceptor‐sympathetic reflex. In this study we determined whether sympathetic premotor neurons in the rostral ventrolateral medulla (RVLM), which have a critical role in the reflex control of sympathetic activity, are activated during air puff stress, a moderate psychological stressor. Secondly, we identified neurons that are activated by air puff stress and that also project to the nucleus tractus solitarius (NTS), a key site for modulation of the baroreceptor reflex. Air puff stress resulted in increased c‐Fos expression in several hypothalamic and brainstem nuclei, including the paraventricular nucleus (PVN), dorsomedial hypothalamus, perifornical area (PeF), periaqueductal gray (PAG), NTS and rostral ventromedial medulla, but not in the RVLM region that contains sympathetic premotor neurons. In contrast, neurons in this RVLM region, including catecholamine‐synthesizing neurons, did express c‐Fos following induced hypotension, which reflexly activates RVLM sympathetic premotor neurons. The highest proportion of NTS‐projecting neurons that were double‐labelled with c‐Fos after air puff stress was in the ventrolateral PAG (29.3 ± 5.5%), with smaller but still significant proportions of double‐labelled NTS‐projecting neurons in the PVN and PeF (6.5 ± 1.8 and 6.4 ± 1.7%, respectively). The results suggest that the increased sympathetic activity during psychological stress is not driven primarily by RVLM sympathetic premotor neurons, and that neurons in the PVN, PeF and ventrolateral PAG may contribute to the resetting of the baroreceptor‐sympathetic reflex that is associated with psychological stress.